Saccharomyces cerevisiae surface display of endolysin LysKB317 for control of bacterial contamination in corn ethanol fermentations - Lu, Shao-Yeh; Liu, Siqing; Patel, Maulik H.; Glenzinski, Kristina M.; Skory, Christopher D. (Frontiers in Bioengineering and Biotechnology, 2023)
Control of bacterial contamination in bioethanol fermentation facilities has traditionally relied on chemical-based products such as hop acids and use of antibiotics. Recent emphasis on antibiotic stewardship has prompted new research into the development of alternative approaches to microbial remediation strategies. We recently described a recombinant peptidoglycan hydrolase, endolysin LysKB317, which inhibited Limosilactobacillus fermentum strains in corn mash fermentation. Here, Saccharomyces cerevisiae EBY100 was used to anchor recombinant LysKB317 using cell surface display with the a-agglutinin proteins Aga1p–Aga2p. Immunostaining and confocal fluorescence were used for localization of the extracellular interface of the cells. Yeast surface-expressed endolysin demonstrated an 83.8% decrease in bacterial cell counts compared to a 9.5% decrease in control yeast. Recombinant S. cerevisiae expressing LysKB317 used for small-scale corn mash fermentation, when infected with L. fermentum, could proactively control bacterial infection for 72 h with at least 1-log fold reduction. Analysis of fermentation products showed improved ethanol concentrations from 3.4% to at least 5.9% compared to the infection-only control and reduced levels of lactic and acetic acid from 34.7 mM to 13.8 mM and 25.5 mM to 18.1 mM, respectively. In an optimized yeast surface display system, proactive treatment of bacterial contaminants by endolysin LysKB317 can improve fermentation efficiency in the presence of L. fermentum contamination.